The Existence of Pesantren Based Technology: Digitalization of Learning in Pondok Pesantren Darul Ulum Kudus - Zafi, Ashif Az; Jamaluddin, Dindin; Partono, Partono; Fuadi, Salis Irvan; Chamadi, Muhamad Riza (Jurnal Pendidikan Agama Islam, 2021)
This research is motivated by developing technology. Pesantren have the choice to adapt to technology or reject it. Both choices have their respective impacts. This study aims to explain the adaptation to the use of technology in the Darul Ulum Pesantren in Kudus and how the position of the Pesantren Kyai after the use of technology. The research method used is a qualitative research method through the process of data collection, data reduction, data presentation, conclusion, and data verification. Search data using interviews, observation, and documentation. The object of this research is the Pesantren program related to the application of technology and the communication process of Kyai with Pesantren residents. The findings of this study state that Darul Ulum Kudus Pesantren is conducting an adaptation process to technological advances by approaching education, digital literacy, and the virtual Qur’an. Pesantren utilizes Whatsapp, Facebook, Instagram, and Youtube. This causes the existence of Pesantren outside to be better, meaning that more people know and know about the programs Pesantren. However, it causes a decrease in the sacredness of the Kyai for his santri. Kyai becomes dialogic and democratic rather than authoritarian. This research implies that Islamic boarding schools that choose to adapt to technological developments will change the authority of the Kyai. But the Kyai also has the authority to make his Pesantren adapt to technology or reject technology.